Molecular Docking and ADMET Study of Phytochemicals as Anticancer Agent towards Alpha 1- Antichymotrypsin Variant DBS-II and Oxidised Quinone Reductase-2 - Patil , Pallavi; Shegokar, Neha; Raut, Pratiksha; Chonde , Aditya (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Objective: The main goals of this study were to do molecular docking and absorption, distribution, metabolism, excretion, and toxicity (ADMET) tests on vanillic acid, ferulic acid, chlorogenic acid, and catechin hydrate. The study aimed to determine the receptor affinity of these drugs using molecular docking simulations, with a focus on the potential anticancer impact of targeting the Alpha 1-Antichymotrypsin Variant DBS-II and Oxidised Quinone Reductase-2. Materials and Methods: Doxorubicin was used as a reference standard for the molecular docking investigations of the compounds, which were performed using Protein Data Bank (PDB) ID: 4ZVM and PDB ID 5OM7. Additionally, we performed ADMET investigations of these drugs using SwissADME and ProTox-II software programmes. Results: Chlorogenic acid exhibited a higher score than the other three compounds with regard to anticancer activity, with scores of -7.869 Kcal/mole for oxidised quinone reductase-2 in complex and -5.941 Kcal/mole for Alpha1-Antichymotrypsin Variant DBS-II, respectively, after the reference drug. ADMET analysis demonstrated the suitability of these compounds for use in pharmaceutical applications. Conclusion: Studies show that all four drugs bind to Oxidised Quinone Reductase-2 (OQR-2) and Alpha 1-Antichymotrypsin Variant DBS-II, which could mean that they can fight cancer. In addition, the toxicity evaluation and ADME analysis reveal how suitable these substances are for use in pharmaceuticals.